HOX genes in ovarian cancer - Kelly Zoë L; Michael Agnieszka; Butler-Manuel Simon; Pandha Hardev S; Morgan Richard GL (BMC, 2011)
Abstract The HOX genes are a family of homeodomain-containing transcription factors that determine cellular identity during development. Here we review a number of recent studies showing that HOX genes are strongly expressed in ovarian cancer, and that in some cases the expression of specific HOX genes is sufficient to confer a particular identity and phenotype upon cancer cells. We also review the recent advances in elucidating the different functions of HOX genes in ovarian cancer. A literature search was performed using the search terms HOX genes (including specific HOX genes), ovarian cancer and oncogenesis. Articles were accessed through searches performed in ISI Web of Knowledge, PubMed and ScienceDirect. Taken together, these studies have shown that HOX genes play a role in the oncogenesis of ovarian cancer and function in the inhibition of apoptosis, DNA repair and enhanced cell motility. The function of HOX genes in ovarian cancer oncogenesis supports their potential role as prognostic and diagnostic markers, and as therapeutic targets in this disease.